Ross's Gulls (Rhodostethia rosea) Breeding in Greenland: A Review, with Special Emphasis on Records from 1979 to 2007 - Egevang, Carsten; Boertmann, David (ARCTIC, 2009)
This review summarizes breeding records of Ross’s gull in Greenland with special emphasis on the period between 1979 and 2007. The review comprises both previously published records (including some published only in Danish) and unpublished reports and breeding records from 2004 and 2006. The majority of the Greenland breeding records fall into two geographically isolated areas that differ in habitat and climate: the Disko Bay area in West Greenland and the Northeast Water Polynya in Northeast Greenland. Despite the fact that antagonistic interactions with arctic terns are common, Ross’s gulls show a nest site preference for the edge of tern colonies, suggesting breeding association between these species. A general increase in breeding records in Greenland since 1978 is most likely the result of increased ornithological effort. Successful breeding has not yet been confirmed, and a Ross’s gull fledgling remains to be seen in Greenland. The Greenland breeding records suggest an opportunistic strategy in choice of breeding site among vagrant and possibly first-time breeders. Nous présentons ici un résumé des enregistrements de reproduction de la mouette rosée au Groenland, plus particulièrement pendant la période s’échelonnant entre 1979 et 2007. Cela comprend des enregistrements déjà publiés (dont certains n’ont été publiés qu’en danois) de même que des rapports inédits et des enregistrements de reproduction pour la période allant de 2004 à 2006. La majorité des enregistrements de reproduction du Groenland touchent des régions géographiquement isolées dont l’habitat et le climat diffèrent : la région de la baie Disko dans l’ouest du Groenland et la région Northeast Water Polynya dans le nord-est du Groenland. Même si des interactions antagonistes avec la sterne arctique s’avèrent courantes, la mouette rosée préfère que son nid se situe en bordure des colonies de sternes, ce qui laisse croire qu’il y a une association de reproduction entre ces espèces. Depuis 1978, l’augmentation générale des enregistrements de ...